Greek women in archaeology: a chronicle of achievement - Kokkinidou , Dimitra; Nikolaidou , Marianna (Journal of Greek Archaeology, 2024)
This article sketches a historic panorama of Greek women’s contributions to archaeology, and elaborates on some of our previously published ideas. In 1993 our first collaborative efforts resulted in the first book on gender in Aegean prehistory, which still remains one of the few syntheses on the topic. In 1998 we recounted the (then) untold achievement of pioneer Greek female archaeologists and their legacy. In 2009 we registered the progress – or absence thereof – towards feminist alignment in a scholarly field that has seen ever-larger female participation since the 1960s. Some fifteen years later, developments call for an updated appraisal of long-standing issues, this time in a more optimistic spirit. Female archaeological activity in Greece, in the course of more than a century, is an extensive terrain to cover. In these pages, we can only highlight selected examples which, we believe, are representative of the whole picture. The narrative is organised in chronological sections, each one starting with a summary of the broader historic context, within which female involvement in archaeology has to be assessed.